An iridium oxide microelectrode for monitoring acute local pH changes of endothelial cells. Issue 12 (21st June 2015) - Ng, Shu Rui; O'Hare, Danny
<x xml:space="preserve">Abstract</x> A microelectrode on a chip was modified to detect the local pH changes of the attached endothelial cells under the stimulation of thrombin.